ASCOPE LABORATORY TEST CORRELATION PROGRAMME FOR OCTANE NUMBER MEASUREMENT IN 1992 - Bustani Mustafa (Scientific Contributions Oil and Gas, 1994)
The ASCOPE Correlation Programme for octane number measurement obtains precision octane number data for gasoline using the CFR engine and the normally used method: ASTM 2699 and IP 237. The test results of the various participating laboratories are subjected to statistical analysis to determine average values, variance, standard deviation and to reject the outliers values. The Grubbs T-test is used for the statistical rejection of outliers. This method is used by both NEG and ASCOPE in their laboratory test correlation programme. The Grubb T-test appears to be quite satisfactory for ASCOPE purposes. The implementation of the Grubbs T-test assures inter-laboratory consistency and this in turn will give the buyer or seller of the gasoline confidence in the quality of the fuel.